(3efGaY GdCYVGA dLGdjfhSs - (3LGdjfhSs
(3ChdgG (B:s
(3HWHjYJg Edi CSad LYdJ GdeLGQi GdJi gjFJ dbPa gPg GdaVhd LfSjf CjVkG s
(3BNQgG (B:s
(3aTHgJ gPg GdebGdI HJdc GdUdGI aGSJYQJ dgG gPG GdGSe , hNJeJ HgG LejY cJGHi ai efGaY GdCYVGA HdZJ GdebGHdI ceG GdebGdI GdSGHYI YTQ ef cJGH LGdjfhS ai efGaYGdCYVGA HMeO Gddg hYhfg s
(3bhHdJ hUMMJ Ydi fSNI cGfJ ddhRjQ GdLdjd CHj HcQ Hf GdUGFZs
(3LRA efgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
GALS - (3GdLRA (B3 - (3U (B106 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B251 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B290 s
Keywords: (3GdWHs